Adeline Ravoux, By Vincent Van Gogh, Cleveland Museum Of Art, 1958.31 - Vincent van Gogh (NC, 2026)
In May 1890, Van Gogh left the south and settled in Auvers, a small town north of Paris, where he rented a room at the inn of Arthur Ravoux. This portrait, completed during the last months of the artist’s life, depicts Ravoux’s 13-year-old daughter, Adeline. Van Gogh wrote that rather than photographic resemblance, he wanted his portraits to convey the “impassioned aspects” of contemporary life through the “modern...
Licence indiquee par Wikimedia Commons
Keywords: oeuvre d'art; musee; Van Gogh